2021
DOI: 10.1177/21582440211032154
|View full text |Cite
|
Sign up to set email alerts
|

How to Run an Empty School: The Experience of Slovenian School Heads During the COVID-19 Pandemic

Abstract: In mid-March 2020, Slovenia declared the COVID-19 epidemic, which led to the closure of schools and the transition to remote education. This article presents the findings of a study conducted during the lockdown among school heads in primary and secondary schools. The authors identify the challenges and issues the school heads faced in the first weeks of the epidemic and examine the positive experiences that may represent examples of good practice for dealing with similar problems in the future. The study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Perhaps the higher scores are the result of more intensive cooperation between the counsellors and the principals with many of the initial questions related to the organisation of distance education. Concurrently, research among principals (Kalin et al, 2021;Skubic Ermenc et al, 2021) showed that, in unpredictable and emergency situations, there was a significant need for a calm, decisive and proactive leader who could effectively manage the situation and provide support to educators. Even in the present research, the counsellors see the principal as a source of support, and, at the same time, they notice a high level of willingness on the part of both principals and teachers to collaborate and to tackle the challenges that have been brought about by remote education together.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the higher scores are the result of more intensive cooperation between the counsellors and the principals with many of the initial questions related to the organisation of distance education. Concurrently, research among principals (Kalin et al, 2021;Skubic Ermenc et al, 2021) showed that, in unpredictable and emergency situations, there was a significant need for a calm, decisive and proactive leader who could effectively manage the situation and provide support to educators. Even in the present research, the counsellors see the principal as a source of support, and, at the same time, they notice a high level of willingness on the part of both principals and teachers to collaborate and to tackle the challenges that have been brought about by remote education together.…”
Section: Discussionmentioning
confidence: 99%
“…Another thing to consider is the quality of the (organisational) support received. While the assessment of quality was not part of the study (REDS was merely asking about its presence), it is possible that the teacher might be dissatisfied with the support, which could contribute to its varying relationship with the outcome variables, and it is conceivable that the support offered might be suboptimal given that the educational system as a whole was ill-prepared for the significant changes to distance learning (Ermenc et al, 2021). Indeed, the insignificant contribution of organisational support to outcome variables within the JDR model during the pandemic is not unprecedented (Karaca et al, 2022), making it an interesting avenue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, these often meant swift and all-encompassing moves to distance learning with ill-defined timelines. In Slovenia, for example, the school closures were comparably long-lasting and happened with little-to-no preparation for either students, teachers, or schools (Ermenc et al, 2021;Klemenčič et al, 2022). Consequently, teachers faced challenges as they had to adapt to working from home, change their instructional methods and/or materials to fit remote learning, and deal with problems their students faced in terms of access and use of ICT -or learn how to use these tools themselves (Kasprzak and Mudło-Głagolska, 2022).…”
Section: The Impact Of Covid-19 On the Work Of Teachersmentioning
confidence: 99%
“…The d igi school initiative, which targets socially disadvantaged pupils, was another Ministry effort to address technical equipment issues. Donors helped collect more p c s for low-income distance learning students (Ermenc et al, 2021). Schools around Slovenia let kids borrow computers.…”
Section: Covid-19 Pandemic Digital Challengesmentioning
confidence: 99%